Impaired AMPA signaling and cytoskeletal alterations induce early synaptic dysfunction in a mouse model of Alzheimer's disease. Issue 4 (6th June 2018) - Baglietto‐Vargas, David; Prieto, Gilberto Aleph; Limon, Agenor; Forner, Stefania; Rodriguez‐Ortiz, Carlos J.; Ikemura, Kenji; Ager, Rahasson R.; Medeiros, Rodrigo; Trujillo‐Estrada, Laura; Martini, Alessandra C.; Kitazawa, Masashi; Davila, Jose C.; et al.
Summary: Alzheimer's disease (AD) is a devastating neurodegenerative disorder that impairs memory and causes cognitive and psychiatric deficits. New evidences indicate that AD is conceptualized as a disease of synaptic failure, although the molecular and cellular mechanisms underlying these defects remain to be elucidated. Determining the timing and nature of the early synaptic deficits is critical for understanding the progression of the disease and for identifying effective targets for therapeutic intervention. Using single‐synapse functional and morphological analyses, we find that AMPA signaling, which mediates fast glutamatergic synaptic transmission in the central nervous system (CNS), is compromised early in the disease course in an AD mouse model. The decline in AMPA signaling is associated with changes in actin cytoskeleton integrity, which alters the number and the structure of dendritic spines. AMPA dysfunction and spine alteration correlate with the presence of soluble but not insoluble Aβ and tau species. In particular, we demonstrate that these synaptic impairments can be mitigated by Aβ immunotherapy. Together, our data suggest that alterations in AMPA signaling and cytoskeletal processes occur early in AD. Most important, these deficits are prevented by Aβ immunotherapy, suggesting that existing therapies, if administered earlier, could confer functional benefits.